The Effect of Slaughter Age and Gender of Broiler Cobb Strain on Body Weight, Carcass Weight, and Carcass Percentage - Purnomo, Agus; Sudarisman, Sudarisman; Prihtiyantoro, Wahyu; Agustin, Citravia (Jurnal Peternakan, 2024)
Demand for chicken consumption in Indonesia tends to increase every year. Broiler chickens were slaughtered at short age than past years, recently about 4 to 6 weeks. Total of 28 to 42 day old broiler chicks were distributed to completely randomized design in factorial scheme (4,5 and 6 weeks old) and 2 (male and female). All of evaluated were live body weight (LBW), carcass weight (CW), and carcass percentage (CP). Analyzed used Two Way analysis of variane (ANOVA) using SPSS with 5 replication. Duncan Multiple Range Test (DMRT) to determine the differences among treatment means.  The result showed that live body weight had unsignificantly effect of sex but affect (P<0.05) to slaughter age (4, 5 and 6 weeks) it was 1460 g, 1881 g and 2310 g. The means of carcass weight with different sex of male and female had unsignificantly effect it was 1.283 g and 1.223, so do the carcass percentage was 69.43 % and 70.15%. This research can be concluded that difference sexing un affect to body weight (1.891 g), carcass weight (1.253 g) and carcass percentage (69.79%), but the female broiler get higher than male broiler. Thus slaughter age affect (P<0.05) to body weight, carcass weight and carcass percentage, at 4 weeks old was tend to decrease but increasily at 5 weeks and 6 weeks old. The best body weight, carcass weight and carcaas percentage at 5 weeks old, according to market demand.